Law Enforcement on Sharia Compliance: a Case Study on The Murabahah Consumptive Financing Agreement of Bank A Syariah - Nurjannah S; Bambang Setiaji (Jurnal IUS Kajian Hukum dan Keadilan, 2021)
Sharia compliance is the basic basis for assessing whether Islamic banks have enforced sharia law. Law enforcement by Islamic banking must reach the element that the bank has implemented the rules of muamalah related to the prohibition of usury and dzolim. The factual phenomenon is fraud in the murabahah consumptive financing contract by Bank A Syariah. This is important to study and analyze considering that law enforcement on sharia compliance in bank A Syariah on contract and financing instruments has an impact on customer and public trust. This research uses normative legal research methods, with a critical legal study approach. The results of the study show that law enforcement is not directly proportional to sharia compliance. There is still a â€œlegal trickâ€ (Hilah) in the murabahah consumptive financing contract. Hilah is part of the legalization of taking usury. Bank A Syariah business activities have not been maximally carried out in the real or productive sector. Productive sectors, such as livestock, food crop agriculture, food and beverage processing industry, and others. Second, murabahah consumptive financing still relies on the pattern of consumptive lending in the form of a privileged civil servant decree as collateral. The object of the contract is money, not the real sector, so that the murabahah contract fraud by Sharia bank A also surfaced. The murabahah contract that is carried out between BA customers and Sharia bank A is one of the cases that justifies Islamic banks only have sharia labels, but their implementation has not been sharia.